Determination of the effect of internet use and e-health literacy on birth worries in pregnant women - Altunkurek, Seyma Zehra; Yilmaz, Semra Tuncay; Tekin, Özlem Moraloğlu (International Journal Of Community Medicine And Public Health, 2024)
Background: This study was carried out to determine the relationship between the internet use of pregnant women and e-health literacy and birth anxiety. Methods: This descriptive study was conducted 313 pregnant Turkish woman in Ankara Turkey, from May 2018 to December 2018. The Introductory Information and internet usage e-health literacy scale (E-HLS) and the Oxford worries about labor scale (OWLS) used to measure participants’ birth anxiety and e-health literacy. To evaluate data that were not normally distributed, additional descriptive statistics, the Mann-Whitney U test, the Kruskal-Wallis analysis test and Pearson correlation analysis were employed. Results: The (E-HLS) scale and the (OWLS) scale and median scores were 29.31±6.34 and 24.59±7.44, respectively. The majority of pregnant women had access to the internet, and had access to internet for the information given by the health care provider is not clear. Fetal development and nutrition delivery were the two most often mentioned topics of interest. We detected statistically significant relationships between Internet usage during pregnancy and income and education status (p<0.05). A moderately positive and statistically significant relationship was detected between e-health literacy and Oxford birth anxiety total score. Conclusions: During antenatal visits and childbirth education classes, health professionals should help increase the e-health literacy of pregnant women, including the abilities to search, understand, and evaluate health information from electronic sources.